2012
DOI: 10.4103/1735-3327.104878
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial evaluating the success rate of ethanol wet bonding technique and two adhesives

Abstract: Background:Composite resin restorations may have a short lifespan due to the degradation of resin–dentin interface. Ethanol wet bonding technique may extend the longevity of resin–dentin bond. The purpose of this one year randomized clinical trial was to compare clinical performance of two adhesives with ethanol wet bonding technique.Materials and Methods:This randomized clinical trial was performed on 36 non-carious cervical lesions in 12 patients restored with composite resin using one of the following appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…19,20 Contemporary adhesives are not able to completely remove water, leading to the dilution of monomers and water sorption of the adhesive layer during aging. 20,21 The EWBT causes a decrease in the diameter of collagen fibrils due to an increase in intramolecular hydrogen bonding and a decrease in matrix volume. This consequently increases the size of interfibrillar spaces, which allows greater impregnation of the adhesive system and hydrophobic monomers.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Contemporary adhesives are not able to completely remove water, leading to the dilution of monomers and water sorption of the adhesive layer during aging. 20,21 The EWBT causes a decrease in the diameter of collagen fibrils due to an increase in intramolecular hydrogen bonding and a decrease in matrix volume. This consequently increases the size of interfibrillar spaces, which allows greater impregnation of the adhesive system and hydrophobic monomers.…”
Section: Discussionmentioning
confidence: 99%
“…14 Few clinical studies have evaluated the EWBT as a dentin pretreatment. 15,16 The use of ethanol has been evaluated with a modified progressive technique 16 and by using two coats of hydrophobic bonding resin, 15 with no significant differences because of the technique in these two clinical studies. In another study, a formulated experimental hydrophobic adhesive containing ethanol in its hydrophobic primer composition resulted in acceptable performance.…”
Section: Introductionmentioning
confidence: 99%
“…17 To the best of the authors' knowledge, only one report on the clinical use of the EWBT with a commercially available hydrophobic adhesive has been published. 15 Moreover, only one study evaluated the cytotoxicity of the EWBT on human pulp cells; the authors concluded that it does not increase pulpal damage when compared with water-wet bonding after 48 hours. 18 Non-carious cervical lesions (NCCLs) represent cervical tooth wear not associated with dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect to be considered is the deficient inter-diffusion of resin within the water-saturated demineralized dentin leaving unprotected or poorly encapsulated collagen fibrils that could be slowly hydrolyzed by endogenous matrix metalloproteinases (MMPs) (Li et al, 2012;Mortazavi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several laboratory researches have shown a promising performance of ethanol-wet bonding technique (EWBT) to improve resin-dentin bonding durability (Sadek et al, 2010a;Li et al), but there are few clinical data about this matter (Mortazavi et al;Araújo et al, 2013;Kuhn et al, 2015). Besides, some unfavorable aspects are mentioned in the literature, such as the time consuming technique, which demands several sequential steps, making the clinical procedure not attractive (Souza Júnior et al, 2015).…”
Section: Introductionmentioning
confidence: 99%